Effect of Low Molecular Weight Oxidized Materials and Nitrogen Groups on Adhesive Joints of Polypropylene Treated by a Cold Atmospheric Plasma Jet - Polášková, Kateřina; Klíma, Miloš; Jeníková, Zdeňka; Blahová, Lucie; Zajíčková, Lenka (Polymers, 2021)
Polypropylene is a typical representative of synthetic polymers that, for many applications including adhesive joints, requires an increase in wettability and chemical surface reactivity. Plasma processing offers efficient methods for such surface modifications. A particular disadvantage of the plasma jets can be the small plasma area. Here, we present a cold atmospheric plasma radio-frequency slit jet developed with a width of 150 mm applied to polypropylene plasma treatment in Ar, Ar/O2 and Ar/N2 We identified two main parameters influencing the tensile strength of adhesive joints mediated by epoxy adhesive DP 190, nitrogen content, and the amount of low molecular weight oxidized materials (LMWOMs). Nitrogen functional groups promoted adhesion between epoxy adhesive DP 190 and the PP by taking part in the curing process. LMWOMs formed a weak boundary layer, inhibiting adhesion by inducing a cohesive failure of the joint. A trade off between these two parameters determined the optimized conditions at which the strength of the adhesive joint increased 4.5 times. Higher adhesion strength was previously observed when using a translational plasma gliding arc plasma jet with higher plasma gas temperatures, resulting in better cross linking of polymer chains caused by local PP melting.
Keywords: cold atmospheric plasma; water contact angle; plasma treatment; X-ray photoelectron spectroscopy; polypropylene; adhesion